KAJIAN ZAT PENGATUR TUMBUH DALAM PERKEMBANGAN KULTUR JARINGAN KRISAN - Astutik Astutik (BUANA SAINS, 2007)
Alar accelerates the growth of aksiler shoots, shortens stem joint and strengthens the stem. Alar addition into the medium is assumed to be able to increase the success of Chrysanthemum tissue culture in quantity and quality. The objectives of this research were: (1) learning and finding the influence of Auksin, Sitokinin, and Alar on number of Chrysanthemum shoots produced. (2) producing a shorter plantlet having a big stem diameter until it is appropriate to be arranged as pot flower. The research used a factorial complete random design consisting of 3 factors. Factor I: Kinds of Auksin (4) are IAA, NAA, IBA, 2,4-D each with the same concentration of 0,1 mg/I. Factor II: Kinds of Sitokinin (2): 1 mg/I Benzylzdenine (BA) and 1 mg/I Kinetin. Factor III: Alar of 0 mg/I and 1 mg/I. Parameters observed when the shoot grows were leaf number, shoot number, plantlet height, stem diameter; when the root grows, root number, root length, and acclimatization success percentage. The results showed that (1) addition of Alar into Chrysanthemum micro-propagation medium had no influence on the shoot number. BA 1 mg/I produced a better shoot number (3,54 shoots/explant) by the 5th week of culture. (2) 1 mg/I Alar application combined with 1 mg/I BA and 0,1 mg/I IAA produced shorter plantlet, followed by the combination of 1 mg/I Kinetin and 0,1 mg/I IBA. (3) the use of 1 mg/I Alar combined with 1 mg/I BA and all kinds of Auksin produced bigger stem diameter plantlet. (4) (1 mg/I) Alar was good to produce Chrysanthemum flower for big stem and shorter plant